Tryptic peptide analysis on nonstructural and structural precursor proteins from Semliki Forest virus mutant-infected cells. - Lachmi, B E (1975)
Analysis of [35S]methionine-labeled tryptic peptides of the large proteins induced by temperature-sensitive mutants of Semliki Forest virus was carried out. The 130,000-molecular-weight protein induced by ts-2 and ts-3 mutants contained the peptides of capsid protein and of both major envelope proteins E1 and E2. The ts-3-induced protein with molecular weight of 97,000 contained peptides of the capsid and envelope protein E2 but not those of E1. Two proteins with molecular weights of 78,000 and 86,000 from ts-1-infected cells did not contain the peptides of the virion structural proteins. They are evidently expressions of the nonstructural part of the 42S RNA genome of Semliki Forest virus.